Platelets and regeneration - B. G. Yushkov (Бюллетень сибирской медицины, 2021)
The review presents the analysis of data proving the role of platelets in the mechanisms of regulation of reparative tissue regeneration. The influence of platelets on damage, apoptosis, and proliferation of cells, as well as on extracellular matrix remodeling, angiogenesis, and neurogenesis is shown. Their  interaction with macrophages in restoring the structure of damaged tissues is assessed. Several regenerative properties of platelets are characterized.